'The interface of the future': Mixed reality, intimate data and imagined temporalities. Issue 1 (January 2022) - Egliston, Ben; Carter, Marcus
This article examines discourses about mixed reality as a data-rich sensing technology – specifically, engaging with discourses of time as framed by developers, engineers and in corporate PR and marketing in a range of public facing materials. We focus on four main settings in which mixed reality is imagined to be used, and in which time was a dominant discursive theme – (1) the development of mixed reality by big tech companies, (2) the use of mixed reality for defence, (3) mixed reality as a technology for control of populations in civil society and (4) mixed reality as a technology used in workplace settings. Across these settings, the broad narrative is that mixed reality technologies afford overwhelmingly positive benefits like efficiency and security through their capture, relay and rendition of data (about the environment, about the body etc.) – affording a form of anticipatory power to the user. The framing of temporality, we argue, is underlain by social and political values, which represent certain interests, but leave others out in the imagination of mixed reality's technological advance.